Objaśnienia Ewangelii według Jana (Skeireins Aiwaggeljons þairh Iohannen) - Leszkiewicz, Bartosz (Vox Patrum, 2026)
The fragmentarily preserved Interpretation of the Gospel according to John are most often considered to be a translation of a lost work by Theodore, bishop of Heraclea Ponticus from the first half of the 4th century. It is one of the few existing texts of Arian theology. It is also the most important, after an incomplete translation of the Bible, testimony to the language of the Goths, who invaded the Roman Empire and established their own states in Italy, Provence, and the Iberian Peninsula. In its present form, the Interpretation consist of eight short and unrelated fragments, commenting on certain pericopes of the Gospel According to St. John in a semi-Arian and anti-Sabellian spirit.